A new genus and two new species of galling aphids (Hemiptera: Aphididae) from Distylium (Hamamelidaceae) in Taiwan - Yeh, Hsin-Ting; Ko, Chiun-Cheng (Zootaxa, 2017)
Cecidological and taxonomic investigations of members of the aphid tribe Nipponaphidini (Aphididae: Hormaphidinae) are proceeding very slowly owing to the rarity of galls and difficulty in distinguishing morphologies. We describe here two new Nipponaphidini species that induce galls on the primary host, Distylium racemosum Siebold & Zucc. (Isu tree, Hamamelidaceae), from Taiwan. One is designated Monzenia minuta sp. n. which induces a closed spherical gall on twigs of D. racemosum. The other one is designated as a new genus, Tripartita gen. n., and new species, formosana sp. n. which can induce open, spindle-like galls on leaves of D. racemosum and also on leaves of Distyliopsis dunnii (J.H.Hemsl.) Endress (Hamamelidaceae). This is the first report of the same hormaphidine aphid species inducing galls on two distinct primary hosts. Here we provide morphological diagnoses and cecidological information for both new species.